Evidence for CP violation in time-integrated D0→h(-)h(+) decay rates. - Aaij, R; Abellan Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; Alvarez Cartelle, P; et al. (2012)
A search for time-integrated CP violation in D(0)→h(-)h(+) (h=K, π) decays is presented using 0.62 fb(-1) of data collected by LHCb in 2011. The flavor of the charm meson is determined by the charge of the slow pion in the D(*+)→D(0)π(+) and D(*-)→D[over ¯](0)π(-) decay chains. The difference in CP asymmetry between D(0)→K(-)K(+) and D(0)→π(-)π(+), ΔA(CP)≡A(CP)(K(-)K(+))-A(CP)(π(-)π(+)), is measured to be [-0.82±0.21(stat)±0.11(syst)]%. This differs from the hypothesis of CP conservation by 3.5 standard deviations.